About the role of the media in the positioning of a resort town - G. D. Avdgyan (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2015)
The author analyzes the most significant channels of the information impact on human consciousness with the purpose to form his motives for choice of a possible resting place.